2008
DOI: 10.1111/j.1365-2427.2008.02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic differences in the essential fatty acid composition of groups of freshwater zooplankton relate to reproductive demands and generation time

Abstract: 1. Marked differences were observed in the total fatty acid concentrations and essential fatty acid (EFA) distributions of co-existing freshwater copepods and cladocerans in four large lake systems (lakes Michigan, Erie, Ontario and Champlain) over two growing seasons. These patterns appeared independent of lake seston EFA composition. 2. Compared to the cladocerans, calanoid and cyclopoid copepods contained significantly higher concentrations of total fatty acids and docosahexaenoic acid (DHA), an EFA abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
88
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 56 publications
(144 reference statements)
18
88
2
Order By: Relevance
“…high abundance of Cryptophyceae rich in long-chain PUFAs in fishless enclosures versus predominance of Chlorophyceae lacking these essential long-chain fatty acids in fish enclosures. This result is consistent with the correlations observed between the essential PUFA content in some zooplankton species and that of their algal diet (Kainz et al 2004;Brett et al 2006;Persson and Vrede 2006;Smyntek et al 2008).…”
Section: Zooplanktonsupporting
confidence: 91%
“…high abundance of Cryptophyceae rich in long-chain PUFAs in fishless enclosures versus predominance of Chlorophyceae lacking these essential long-chain fatty acids in fish enclosures. This result is consistent with the correlations observed between the essential PUFA content in some zooplankton species and that of their algal diet (Kainz et al 2004;Brett et al 2006;Persson and Vrede 2006;Smyntek et al 2008).…”
Section: Zooplanktonsupporting
confidence: 91%
“…For instance, copepods and cladocerans have different metabolic means to cope in cold temperatures. Copepods are able to change their cellular components to more highly unsaturated fatty acids in winter, while cladocerans rely on different fatty acids to maintain cellular fluidity (Smyntek et al 2008;Mariash et al in press). These physiological adaptations ultimately affect diet and feeding rates of cold-tolerant species, which was also the case in this study, where copepods in cold winter temperatures stopped feeding but D. umbra continued feeding on heterotrophic food items.…”
Section: Discussionmentioning
confidence: 99%
“…Tough correlations among seston FA profiles in polar lipids and those in Daphnia have been shown in the field study [4].Moreover, Moreover, few authors have been reported a mismatch between FA composition of zooplankton and its food in natural water bodies [10], [1].…”
Section: Introductionmentioning
confidence: 98%
“…Zooplankton plays a key role in the transfer of PUFA to organisms such as fish [1]. The accumulation of PUFA an invertebrate prey then influences fish production significantly [2].…”
Section: Introductionmentioning
confidence: 99%